(untitled) (Fiep Bulletin - online, 2014)
This article shows the result of a research that was performed by Centro Universitario Feevale with members of Community Action Program "Children of Canudos", proportionate by Physical Education Course. The plain objective of the institutional research is to inquire how the Extension Projects are offered to the community. Within this program we choose the Capoeira course to carry through a multidisciplinary view. The used methodology was the Qualitative, Descriptive, Interpretative using like instruments of data collect, the half-structuralized interview, not participant observation and the field diary. The Collaborators of this investigation have been 10 children who participate since of the beginning of the project Capoeira six years ago.